Laparoscopic pancreaticodoudenectomy: An excellent approach in elderly patients, a multicenter, comparative study. Issue 38 (18th September 2020) - Hendi, Maher; Mou, Yiping; Lu, Chao; Pan, Yu; Zhang, Bin; Chen, Ke; Xu, Xiaowu; Zhang, Renchao; Zhou, Yucheng; Jin, Weiwei
Abstract: Background: Management of malignant diseases in elderly patients has become a global clinical issue because of increased life expectancy worldwide. Advancements in surgical techniques and perioperative management have reduced age-related contraindications for LPD. Past articles have reported that elderly patients undergoing laproscopic pancreatoduodenectomy (LPD) are at an increased risk compared to younger patients. The aim of this article is to compare a multicenter center risk of LPD in elderly and nonelderly patients. Methods: Retrospective review (n = 237) of perisurgical outcomes in patients undergoing LPD during the months of September 2012 to December 2017. Outcomes in elderly patients (aged ≥75 years) were compared with those in nonelderly patients. Results: Transfer to ICU was more frequent in elderly patients (odds ratio [OR] 6.49, P  = .001) and the mean hospital stay was longer (21.4 days compared with 16.6 days), ( P   =  .0033) than for nonelderly patients. There was no statistically significant difference in operation time ( P   =  .494), estimated blood loss ( P   =  .0519), blood transfusion ( P   =  .863), decreased gastric emptying ( P  = .397), abdominal pain ( P   =  .454), food intake ( P  = .241), time to self-ambulation ( P   =  1), reoperation ( P   =  .543), postoperative pancreatic fistula (POPF) grade A ( P   =  .454), POPF grade B ( P   =  .736), POPF grade C ( P   =  .164), hemorrhage ( P   =  .319), bile leakage ( P   =  .428), infection ( P   =  .259), GI bleeding ( P   =  .286), morbidity ( P   =  .272) or mortality ( P   =  .449) between the 2 groups. Conclusions: Elderly patients who underwent LPD in this study had good overall outcomes after LPD that were similar to young patients. The perioperative and long-term outcomes of LPD are not worse. Rates of ICU admission and hospital stays increased in elderly patients undergoing LPD when compared with nonelderly ones. LPD can be performed on elderly patients with similar outcomes as younger patients; therefore, age itself should not be a contraindication for LPD for pancreatic cancer, but it suggests that elderly patients with comorbidities should be more stringently selected for surgery.